O20 Thrombectomy for medium vessel occlusions: treatment effect of successful recanalization on long term functional outcome. (29th August 2022) - Kniep, H; Bechstein, M; Broocks, G; Brekenfeld, C; Flottmann, F; Deb-Chatterji, M; Meyer, L; Hanning, U; Thomalla, G; Fiehler, J; Gellißen, S
Abstract : Introduction: Treatment effects of successful recanalization after mechanical thrombectomy (MT) have been evaluated for acute ischemic strokes with large vessel occlusion. However, for medium-vessel occlusions (MeVO) treatment effects of successful recanalization have not been investigated in detail. Aim of the study To quantify treatment effects of different degrees of recanalization after MT in MeVO on long term function outcome. Methods: All patients enrolled in the German Stroke Registry from 05/2015 to 12/2019 with MeVO of the middle cerebral artery and availability of the relevant data points were included. The treatment effect of different degrees of recanalization (TICI scores) was analyzed using established binarized outcome metrics (good outcome: 90d mRS≤2) and linearized outcome metrics defined as the mRS increase pre-stroke to 90d. Treatment effects were assessed using double robust inverse-probability-weighted regression-adjustment estimators for multivalued treatments. Results: 597 patients fulfilled the inclusion criteria. 97 (16%) patients had TICI<2b with good outcome in 19%. 194 (33%) patients had TICI 2b and 296 (50%) had TICI 3. For both cohorts, percentage of good outcome was 55%. Covariate-controlled treatment effect estimation suggests that TICI 2b recanalization increases probability of good long-term functional outcome from 27% to 58% (31 pp). Pre-stroke to 90d mRS increase was reduced by 1.0 mRS points. Full recanalization with TICI 3 did not further increase probability of good outcome and did not further reduce stroke-related mRS increase. Conclusion: TICI 2b recanalization in MeVO increased probability of good outcome from 27% to 58%, TICI 3 recanalization did not further improve prognosis. Do you have any conflict of interest to declare? : Yes Conflict of Interest Statement: Helge Kniep and Fabian Flottmann are consultants for Eppdata. Milani Deb-Chatterji has received research grants from the Werner Otto Stiftung. Götz Thomalla received fees as consultant from Acandis, Bayer, and Portola, and fees as lecturer from Acandis, Alexion, Amarin, Bayer, Boehringer-Ingelheim, BristolMyersSquibb, Daiichii Sankyo, Portola, and Stryker. Jens Fiehler received research support from: German Ministry of Science and Education (BMBF), German Ministry of Economy and Innovation (BMWi), German Research Foundation (DFG), European Union (EU), Hamburgische Investitions- und Förderbank (IFB), Medtronic, Microvention, Route92, Stryker. He is consultant for: Acandis, Bayer, Cerenovus, Covidien, Medtronic, Microvention, Penumbra, Phenox, Stryker and stock holder of Tegus Medical.